Characterization of Infectious Laryngotracheitis Virus Isolates from Turkey by Molecular and Sequence Analysis - Can-Sahna, Kezban; Abayli, Hasan; Ozbek, Remziye; Tonbak, Sukm; Bulut, Hakan (Univ Agriculture, Fac Veterinary Science, 2020)
Infectious laryngotracheitis (ILT) is an economically important respiratory disease affecting the poultry industry worldwide. The aim of this study was to characterize the Turkish ILT virus (ILTV) isolates by sequencing and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). ILTV isolates obtained from laying hens in Turkey in 2003 and 2018 were used in this study. The isolates were analyzed for ICP4, gG, gE and TK gene regions by PCR. The amplification products were used in RFLP analysis to determine the differences among the isolates. Sequence analyses of TK and ICP4 regions were carried out and a phylogenetic tree was formed by using the Maximum Likelihood method. Nucleotide identity values were then calculated among five isolates and other strains/isolates in Genbank. In addition, about 200 amino acid sequences of the start and end regions of the ICP4 gene were compared to other strains in Genbank. PCR-RFLP analysis indicated that Turkish ILTV isolates were low-virulent. In general, the nucleotide sequence similarities of the TK and ICP4 gene regions among Turkish isolates and others was more than 95% (lower in some Egyptian and Bangladeshi strains, 41 and 45% respectively); in the amino acid sequence, it was close to 100%. As a result, PCR-RFLP results were similar in many gene regions. However, evolutionary analysis of ICP4 and TK gene regions did not yield reliable results based on geographic distribution or pathogenicity levels. For this purpose, different methods, such as Bayesian analysis or the involvement of samples from different gene regions can yield more reliable results, just like whole-genome sequences. (C) 2020 PVJ. All rights reserved
Keywords: ILTV; PCR-RFLP; sequence analysis; Turkey